2002
DOI: 10.2527/2002.801129x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of slaughter weight and sex on yield and quality grades of Hanwoo (Korean native cattle) carcasses1

Abstract: To assess the effects of slaughter weight and sex on APGS (Animal Products Grading Service) quality and APGS yield grade of Korean Hanwoo (n = 20,881) cattle, data were collected from cow, bull, and steer carcasses during a 1-yr period. Factors used to determine quality grade (marbling, meat color, fat color, texture, and overall maturity score) and yield grade (cold carcass weight, adjusted fat thickness, and longissimus muscle area) by the Korean grading system were recorded. Both yield and quality grades we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
54
1
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 8 publications
11
54
1
11
Order By: Relevance
“…These can be attributed to the higher live weight of the 32 mon old cattle. The current results were in agreement with the findings of Park et al (2002) who reported that yield grade of Hanwoo cattle improved with increased animal weight and that yield grade and ribeye area are positively correlated (r=0.51). However, Park et al (2002) observed that there was no further increase in yield for cattle weighing more than 551 kg.…”
Section: Carcass Characteristicssupporting
confidence: 93%
See 3 more Smart Citations
“…These can be attributed to the higher live weight of the 32 mon old cattle. The current results were in agreement with the findings of Park et al (2002) who reported that yield grade of Hanwoo cattle improved with increased animal weight and that yield grade and ribeye area are positively correlated (r=0.51). However, Park et al (2002) observed that there was no further increase in yield for cattle weighing more than 551 kg.…”
Section: Carcass Characteristicssupporting
confidence: 93%
“…The current results were in agreement with the findings of Park et al (2002) who reported that yield grade of Hanwoo cattle improved with increased animal weight and that yield grade and ribeye area are positively correlated (r=0.51). However, Park et al (2002) observed that there was no further increase in yield for cattle weighing more than 551 kg. This is because the cattle that they evaluated within live weight classes were a mixture of steers, bull and cows that are of different ages.…”
Section: Carcass Characteristicssupporting
confidence: 93%
See 2 more Smart Citations
“…The ribeye area in the present study was within the range of 8 -9.4 cm 2 reported by Hagos and Melaku (2009) for Afar rams. Ribeye area is affected by the weight and muscularity of the live animal (O'Rourke et al, 2004) and it is increased with carcass weight (Park et al, 2002). The backfat thickness in the present study was slightly lower but within range of of 2.8 -7 mm reported by Degu et al (2009) for Tigray highland sheep fed cactus (Opuntia ficus-indica)-teff straw and supplemented with isonitrogenous oil seed cakes.…”
Section: Carcass Characteristicssupporting
confidence: 43%